Analysis of Tensile Strength of Welding SS400 Steel with Varying Thickness - Putri, Destyariani Liana; Siburian, Christoper (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Technology in the construction sector is increasingly developing and advancing at this time. The construction that we often encounter is steel construction. In steel construction, we most often encounter metal joining or welding processes. Shield Metal Arc Welding (SMAW) is a metal joining process that uses electrical energy as a source of heat and is assisted by electrodes. In this journal, I modeled the welding results using Ansys Workbench. The modeling aims to carry out a tensile test simulation to determine the tensile strength of SS400 Steel with a plate thickness of 8 mm, 10 mm, and 12 mm. This research began with creating a model in ANSYS by referring to the SNI 8389:2017 standard. After the modeling is complete, then input the materials to be used, mesh the model with a size of 2 mm, and determine the fixed support and force of 100,000 (N/m2). Then we carried out a tensile test simulation to get the normal stress and total deformation values. The largest normal stress value was obtained on the 8 mm plate, which was 3845.4 MPa and the largest total permit value was obtained on the 8 mm plate, which was 0.28271 mm. The conclusion from this test is that the smaller the cross-sectional area of a model, the higher the pressure it will experience, so it will experience higher stress and will experience cooling more easily.